Biological Characteristics, Hazard Patterns, and Control Measures of Aegilops tauschii, the Most Harmful Weed in Chinese Wheat Fields - Yaling Geng; Chencan Wang; Jiangwei Han; Yiyun Ban; Zongran Su; Linghui Wang; Jing Xu; Libing Yuan (Plants)
The control of A. tauschii is critical to ensuring food security. This study investigated a range of different aspects of the biology of A. tauschii, including its emergence characteristics, population development dynamics, and its impact on wheat yield. Moreover, the efficacy of different herbicides and cultural control measures for managing A. tauschii was explored. Through laboratory cultivation and statistical analysis of the emergence rate of A. tauschii, it was found that its emergence rate significantly increased when temperatures ranged from 10 °C to 20 °C and the environmental osmotic potential fell between −0.1 MPa and −0.5 MPa—conditions similar to those found in wheat fields. Additionally, by recording the emergence rates at different depths, A. tauschii emergence was found to occur optimally at a sowing depth of 1–5 cm, which aligns with the shallow rotary tillage currently employed in wheat production. The weed was also found to be tolerant to weakly acidic and alkaline environments, while also presenting with moderate salt tolerance. Through field experiments, it was found that, upon spreading to new areas, A. tauschii rapidly expanded its population size. While its impact on wheat yield was relatively mild during the early stages of growth, it escalated to severe outbreaks with the passage of time. Field experiments were conducted to test the efficacy of five herbicides on weed control. The analysis indicated that Mesosulfuron-methyl was the only effective herbicide in controlling A. tauschii. Adopting three two-year-three-crop rotation patterns reduced the density of A. tauschii from 186 stems/m2 to 11–15 stems/m2. Watering-induced emergence also proved effective. The most effective watering was performed 15 days before sowing. Deep plowing was another effective measure. The deeper the plowing, the lower the emergence of A. tauschii. Delayed sowing time resulted in the additional suppression of the emergence of A. tauschii.